Mixing processes in modern estuarine sediments from the Gulf of Khambhat, western India. (March 2018) - Saha, Sourav; Burley, Stuart D.; Banerjee, Santanu
Abstract: Sandy and muddy detritus from two distinctive end-member provenance terrains, basaltic and granitic, are transported to the estuaries of the Gulf of Khambhat by fluvial discharge and opposing tidal currents making this embayment ideal for investigating the effects of mineralogical and geochemical mixing on sediment composition in estuarine depositional systems. Rivers flowing predominantly from the north over Precambrian metasediments and granites supply a felsic plutoniclastic sand to the gulf, whilst a mafic volcaniclastic sand, sourced by Deccan basalts, is transported by rivers draining the Western Ghats and from the local coastal erosion in the southern part of the gulf. Sediments from the Tapti estuary are rich in basaltic rock fragments (∼50%) and are characterised by a distinctly basaltic source composition (La/Sc∼0.25–0.86, Th/Sc∼0.12–0.40, Cr/Th∼13–121, Eu/Eu*∼0.93–1.68 and LREE/HREE∼2.96–6.57). By contrast, the sediments of the Sabarmati inner estuary are rich in quartz grains (80%) as evident from the major and trace element compositions (La/Sc∼1.38–6.63, Th/Sc∼0.58–2.98, Cr/Th∼0.58–19.39, Eu/Eu*∼0.46–0.86 and LREE/HREE∼2.90–11.40). The detrital compositions of the remaining major estuaries, the Narmada, Dhadhar and Mahi, scatter across a broad range in a QFR diagram and contain varying amounts of quartz, feldspar and rock fragments. In the Narmada Estuary the mixed signature characterised by REE values including Eu/Eu* (∼0.42–2.28) and LREE/HREE (∼4.37–14.80) is caused by the presence of diverse rock types that crop out in the source area. In the Mahi estuary, which largely flows across felsic source terrains the compositional signature is controlled by mixing of felsic detritus from riverine input with mafic sediments from seaward side in the estuary. The two end-member detrital compositions, plutoniclastic and volcaniclastic, are mixed in the macro-tidal estuaries. Mixing of sediment takes place where fluvial currents and tidal flows interact and the proportion of mixing varies systematically from outer to central to inner estuary. A high degree of mixing of felsic sediments with Deccan basalt derived sediments takes place in the outer estuary resulting in felsic:mafic ratios of ∼40:60. Sediments in the central estuaries (∼65:35) and in the fluvial-dominated inner estuaries (∼90:10) are characterised by moderate to minor degrees of mixing. The mixing in estuaries is systematic and is reflected in both the mineralogy and geochemistry of the sediments. Provenances of ancient estuarine successions should therefore be interpreted with great care incorporating awareness of the mixing processes which influence sediment compositions to different degrees in estuaries, especially those characterised by strong tidal currents. Highlights: The Gulf of Khambhat receives detritus from two distinct outcropping source lithotypes: basalt and granite. Two end members petrological provinces are mixed in the macro-tidal estuaries. Tapti estuary sediments are volcaniclastic rich in basaltic grains whereas Sabarmati inner estuary sands are quartzose. Sediment composition of other major estuaries scatter across a range of Q:F:R detrital modes and geochemical values. The compositional mixing processes varies systematically from outer to inner estuary.